2014
DOI: 10.1016/j.bbagen.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella enterica ZinT structure, zinc affinity and interaction with the high-affinity uptake protein ZnuA provide insight into the management of periplasmic zinc

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Background: In Gram-negative bacteria the ZnuABC transporter ensures adequate zinc import in Zn(II)-poor environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 48 publications
(78 reference statements)
6
70
1
Order By: Relevance
“…The periplasmic protein ZinT has also been implicated in maintaining zinc homeostasis in the periplasm, although its precise role is still unclear. The most recent results suggest that ZinT functions in conjunction with ZnuABC to import zinc, perhaps by maximizing efficient transfer of zinc to ZnuA (17)(18)(19)(20). In support of this hypothesis, ZinT forms a complex with ZnuA in vitro but only in the metallated form (19,20).…”
supporting
confidence: 50%
See 2 more Smart Citations
“…The periplasmic protein ZinT has also been implicated in maintaining zinc homeostasis in the periplasm, although its precise role is still unclear. The most recent results suggest that ZinT functions in conjunction with ZnuABC to import zinc, perhaps by maximizing efficient transfer of zinc to ZnuA (17)(18)(19)(20). In support of this hypothesis, ZinT forms a complex with ZnuA in vitro but only in the metallated form (19,20).…”
supporting
confidence: 50%
“…8). A detailed biophysical investigation of the ZnuA-ZinT complex combining x-ray crystallography, analytical ultracentrifugation, and x-ray scattering spectroscopy suggested that the His-rich loop of ZnuA is required for complex formation and that it fits into a hydrophobic cleft leading to the zinc site of ZinT (20). These data suggested a model of metal transfer from ZinT to ZnuA requiring the participation of metal ligands on the His-rich loop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PhtD, the most highly conserved Pht protein across pneumococcal strains, contains five His triad (HT) motifs, and each motif is thought to bind one Zn 2ϩ ion (8). Loisel et al produced a truncated derivative of PhtD containing only one HT motif and determined the affinity of the fragment for Zn 2ϩ to be 131 Ϯ 10 nM, which is weaker than that of AdcA (2.4 Ϯ 0.1 nM) and other Zn 2ϩ -binding cluster A-I SBPs (4,8,16). This is consistent with the model for Zn 2ϩ transfer to the higher-affinity site of a Zn 2ϩ -binding SBP for transport into the bacterial cell.…”
mentioning
confidence: 99%
“…This suggests that the inter-domain contacts observed in the crystal are not present in solution, and that the two domains move independent of one another, attached by a flexible linker. This differs from previous solution studies on S. enterica AdcA, which found that the separate ZinT and ZnuA domains formed a stable interaction (55). Our data suggests that in S. pneumoniae AdcA, any such interaction is transient, but does not preclude the possibility that they interact in specific circumstances such as Zinc shortage.…”
Section: Discussioncontrasting
confidence: 56%